Environmental characterization of a dredging disposal site on the continental shelf of Espírito Santo, Brazil - Lagedo, Fillipi Brandão; Dias, Gilberto Tavares de Macedo; e Silva, Rafael Cuellar de Oliveira; Bertoncini, Áthila Andrade; Oliveira, Uirá Cavalcante; da Fonseca, Estefan Monteiro (Quaternary and Environmental Geosciences, 2021)
Dredge material placement is among the major problems in coastal management. Sedimentation caused by dredge-spoil disposal presents a series of impacts, including the burial of benthos and the suffocation of filter-feeding benthic organisms. To minimize dredging impacts, studies in dredging disposal sites shall be performed to allow better approaches to adverse ecological risks. The goal of the present study was to map the sea bottom environment of a potential dredge disposal site by performing its geomorphology and ecology characterization, in the continental shelf of Espírito Santo state. Acoustic images were obtained using side scan sonar to characterize sediment texture and the geometry of deposits, along with a bathymetric survey. Additionally, underwater footage provided images and the description of the biota communities. The bathymetric survey revealed a relatively plain and homogenous bottom, with the presence of a paleochannel. Smooth elevations, with approximately 0.50m high, were found and characterized as calcareous biogenic concretions, among benthic and nektonic organisms. The organisms revealed a heterogeneous composition and a scattered distribution throughout the sampling stations, with the presence of a threatened species.